2019
DOI: 10.12659/msm.912766
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-to-High-Density Lipoprotein Cholesterol Ratio and Systemic Inflammation in Patients with Idiopathic Pulmonary Arterial Hypertension

Abstract: BackgroundIdiopathic pulmonary arterial hypertension (IPAH) patients are characterized by elevated triglyceride (TG)-to-HDL cholesterol (HDL-C) ratio, which has been proposed to be an important prognostic factor in this population. The mechanism of this phenomenon remains unknown. We therefore investigated the potential determinants of increased TG/HDL-C ratio in IPAH patients.Material/MethodsWe prospectively recruited consecutive clinically stable IPAH patients between January 2016 and February 2017. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
5
27
0
Order By: Relevance
“…In this context, TG/HDL may be a useful clinical parameter by linking four separate conditions such as inflammation, dyslipidemia, hyperglycemia and atherosclerosis in the only appropriate definition of ‘atherometabolic disease’. This concept is in line with previous findings focused on TG/HDL and these mentioned pathophysiological disorders 40,41 : Salazar et al found that high TG/HDL was able to identify subjects with insulin resistance and a greater cardiometabolic risk in a large cohort of individuals. Moreover, Jonas et al showed that subjects with an increased TG/HDL had a greater amount of inflammatory cytokine plasma levels such as IL‐1β, IL‐6 and MCP‐1 than low TG/HDL subjects in a cohort of idiopathic pulmonary arterial hypertension subjects.…”
Section: Discussionsupporting
confidence: 90%
“…In this context, TG/HDL may be a useful clinical parameter by linking four separate conditions such as inflammation, dyslipidemia, hyperglycemia and atherosclerosis in the only appropriate definition of ‘atherometabolic disease’. This concept is in line with previous findings focused on TG/HDL and these mentioned pathophysiological disorders 40,41 : Salazar et al found that high TG/HDL was able to identify subjects with insulin resistance and a greater cardiometabolic risk in a large cohort of individuals. Moreover, Jonas et al showed that subjects with an increased TG/HDL had a greater amount of inflammatory cytokine plasma levels such as IL‐1β, IL‐6 and MCP‐1 than low TG/HDL subjects in a cohort of idiopathic pulmonary arterial hypertension subjects.…”
Section: Discussionsupporting
confidence: 90%
“…In our recent study of 66 idiopathic PAH patients, we showed that HDL was able to predict pulmonary artery vasoreactivity and long-term response to calcium channel blocker therapy in patients with newly diagnosed disease. Additionally, we demonstrated that lower levels of HDL-C are correlated with inflammatory cytokines; this indicates that chronic inflammation can mediate the relationship between HDL-C and function of pulmonary vasculature [59,85]. The vasoprotective role of HDL was also recently described in 90 patients with chronic thromboembolic pulmonary hypertension (CTEPH).…”
Section: Hdl and Pulmonary Vascular Disease Severitymentioning
confidence: 80%
“…In the last years, impaired glucose and insulin metabolism was proposed as a novel risk factor in pathobiology of PAH [34,37]. Recent studies in PAH patients reported a specific pattern of metabolic alterations, including insulin resistance defined as elevated triglyceride to HDL cholesterol ratio [34,59], glucose intolerance, and a blunted insulin response to an oral glucose load [60]. The exact link between altered glucose metabolism and smooth muscle cell proliferation in pulmonary vascular disease is still under investigation.…”
Section: Hdl and Insulin Resistancementioning
confidence: 99%
“…However, patients with PH showed a lower weight and body mass index (BMI). Given the accumulating evidence that PH is a systemic metabolic disease characterized with dyslipidemia (Hemnes et al, 2019; Heresi, Aytekin, Newman, DiDonato, & Dweik, 2010; Jonas, Magon, Podolec, & Kopec, 2019; Yuditskaya et al, 2009), we tested whether serum ApoA5, one lipoprotein is closely related with TG metabolism and metabolic syndrome, has been changed in the patients with PH. We found that there was a decrease of ApoA5 in patients with PH compared with CT group ( p < .001; Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…This study started with a clinical finding that ApoA5 was decreased in the serum of patients with PH. From the previous study, we have known that hypoxia may play an important role in energy and lipid metabolism that showed as increased TG/HDL ratio (Jonas & Kopec, 2019; Jonas et al, 2019). Our study also showed an increase of the TG/HDL ratio; however, the characteristic was a significant decrease of HDL and no differences of the TG.…”
Section: Discussionmentioning
confidence: 99%